Towards a gradual scale of vowel reduction: a pilot study - Kul, Małgorzata (Versita, 2010)
The study reports the results of an acoustic analysis of vowel reduction of the /iː/ vowel, considering all three traditionally explored aspects of vowel reduction, i.e. duration, F1 and F2 in read speech produced by 12 native speakers of English. Starting from the observation that the standard literature considers only duration as a proxy for overall reduction, the aim of the study is to verify whether duration, F1 and F2 exhibit reduction (construed as shortening of duration and centralization of formants, respectively) to the same degree. The r test reveals the lack of a robust linear correlation between duration, F1 and F2, the highest value being 0.51 (the correlation between duration and F1) and 0.24 (the correlation between duration and F2), neither of which is a strong correlation. In light of the results, the study seeks to establish a gradual scale of vowel reduction, combining the spatial and the temporal aspects by means of averaging the distances between the least and the most reduced tokens across duration, F1/F2 on an equal basis. The resulting degree is expressed on a scale of reduction, ranging from 0 (no reduction whatsoever) to 100 per cent (reduction to schwa).
Keywords: Vowel reduction; Reduction measure